2017
DOI: 10.1590/s1678-9946201759007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of latex and purified papain from Carica papaya against Strongyloides venezuelensis eggs and larvae

Abstract: Latex from Carica papaya is rich in bioactive compounds, especially papain, which may help to control parasitic diseases. This study evaluated the efficacy of latex from C. papaya and purified papain against Strongyloides venezuelensis. The Egg Hatching Test (EHT) and the Larval Motility Test (LMT) using fresh and frozen latex (250mg/mL), lyophilized latex (34mg/mL), and purified papain (2.8 mg/mL) were performed. Albendazole (0.025 mg/mL) and ivermectin (316 ppm) were used as positive controls. EHT and LMT we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…In this study, we demonstrated that the negative controls (water and DMSO 1%) showed 62.7% and 69.4% inhibition of S. venezuelensis egg hatching, respectively; however, a higher number of larvae were observed in relation to other tested compounds of S. guianensis. These results were similar to the findings of negative controls in other IEH tests of the same species (Moraes et al ., 2017). This study suggested that IEH caused by negative controls was due to the isolation of the eggs from another environment that was not faeces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated that the negative controls (water and DMSO 1%) showed 62.7% and 69.4% inhibition of S. venezuelensis egg hatching, respectively; however, a higher number of larvae were observed in relation to other tested compounds of S. guianensis. These results were similar to the findings of negative controls in other IEH tests of the same species (Moraes et al ., 2017). This study suggested that IEH caused by negative controls was due to the isolation of the eggs from another environment that was not faeces.…”
Section: Resultsmentioning
confidence: 99%
“…The ethanol extract was the S. guianensis sample that suppressed larval motility the most strongly, inhibiting larval motility by 88.4% at the lowest concentration tested. These findings were consistent with the inhibitory effects of Spondias lutea ethanol extract and fractions against S. venezuelensis adult females (Medeiros, 2014), and Carica papaya latex and purified papain against L3 larvae (Moraes et al ., 2017). WAAVP classifies an anthelmintic compound as highly and moderately effective when it inhibits >90.0% and 80.0–90.0% of parasite activity, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In general, parasite resistance to medications routinely used in clinical practice has prompted the search for new alternatives, including the use of plant-derived extracts containing antiparasitic compounds 6,7 . C. papaya stands out among the plants used for the production of folk medicines due to its anthelmintic action, as established in a preliminary survey about the control of intestinal parasites in Africa 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The anthelmintic activity of this plant has been attributed to carpasemine, carpaine-like alkaloids and seed glucosinolates that yield benzyl isothiocyanate, which exert ovicidal and larvicidal effects 9,10 . C. papaya latex and purified papain are effective against S. venezuelensis eggs and larvae and can be used as therapeutic alternatives for the control of strongyloidiasis 7 . Considering the anthelmintic potential of C. papaya against other gastrointestinal nematodes, the present study aims to examine the in vitro ovicidal and larvicidal activity of C .…”
Section: Introductionmentioning
confidence: 99%
“…A papaína purificada apresentou ação dose-dependente eficaz contra ovos e larvas infectantes em estudos in vitro, sugerindo potencial alternativa terapêutica na estrongiloidíase. No entanto, são necessários ensaios para avaliação da citotoxicidade da papaína em linhagens de células humanas(MORAES et al, 2017).Após os testes de screening para escolha da concentração ideal de tratamento para o parasito, foi avaliado o potencial da toxina para induzir a morte celular por diferentes abordagens, tais como autofagia e apoptose.A autofagia é um tipo de morte celular programada em que a marcação com MDC evidencia o processo autofágico induzido pela BnSP-6, sugerindo um papel significativo da autofagia no processo de morte celular do parasito. Por outro lado, a marcação com PI em larvas infectantes e fêmeas partenogenéticas sugere uma resposta tardia semelhante à apoptose no mecanismo de morte celular induzido pela BnSP-6 contra S. venezuelensis.Como demonstrado por Azevedo et al(2016), a BnSP-6 apresentou ação tóxica contra as células de cancer de mama e também induziu autofagia e apoptose celular.…”
unclassified